2020
DOI: 10.21831/economia.v16i2.30661
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Capital Structure on Company Financial Performance

Abstract: This study aims to examine the effect of capital structure on the company's financial performance particularly in manufacturing companies listed on the Indonesia Stock Exchange for the 4 years period from 2014 to 2018. Capital structure is measured by Market Total Leverage (MTLEV), Market Long-Term Leverage (MLLEV) and Market Short-Term Leverage (MSLEV). On the other hand, the company's financial performance is measured by Return on Equity (ROE) and Price to Book Value (PBV). The populations in this study are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
0
4
0
1
Order By: Relevance
“…Shindu et al (2014) also show that Leverage shows a positive relationship with firm performance measures. It is also strengthened by the findings of Nini et al (2020) who see the effect of choosing a company strategy using debt financing on corporate financial performance on the Indonesian Stock Exchange.…”
Section: H1: the Firm Strategy Affects The Capital Structure The Infl...mentioning
confidence: 89%
“…Shindu et al (2014) also show that Leverage shows a positive relationship with firm performance measures. It is also strengthened by the findings of Nini et al (2020) who see the effect of choosing a company strategy using debt financing on corporate financial performance on the Indonesian Stock Exchange.…”
Section: H1: the Firm Strategy Affects The Capital Structure The Infl...mentioning
confidence: 89%
“…Based on the explanation of the phenomenon, this research is a development of previous research by Husada and Handayani (2021), Giannopoulos et al (2022), Hanim et al (2018), Nini et al (2020), Manurung and Wijaya (2022), Almashhadani and Almashhadani (2022), andAlabdullah (2021). The novelty of this study is that the authors use different objects and places.…”
Section: Introductionmentioning
confidence: 84%
“…In contrast, Junius et al (2020) and Ghazali and Zulmaita (2020) stated that Environmental, Social, and Governance Disclosure has no effect on a company's financial performance. Regarding capital structure, Heliola et al (2020); Aulia et al (2018) found that capital structure has a significant positive effect on financial performance, while Nini et al (2020), Mohammad et al (2019) stated that capital structure has a negative and significant effect on the company's financial performance. For managerial ownership, Fibriani et al (2022), Almashhadani and Almashhadani (2022), Suartama and Sukartha (2020), and Loen (2022) found a positive and significant effect on financial performance, whereas Astari and Suputra (2019) stated that managerial ownership has negative effect, and Manurung and Wijaya (2022) found no effect.…”
Section: Introductionmentioning
confidence: 99%
“…Besides that, the cost of business financing, as well as its accessibility and availability, is a crucial component that stimulates sustainable value creation (Kamau, 2021). In another study conducted by Nina et al (2020) capital structure has a negative and http://www.eafj.periodikos.com.br/ significant effect on the company's financial performance. The findings of this study were in line with the agency theory on increase in debt leading to increase in agency costs through the increase of interest rate of debt from creditors.…”
Section: Literature Reviewmentioning
confidence: 96%